In-field Verification of the Applicability of MEMS-IMU Accelerometers for Monitoring of Mining-induced Seismic Activity - Stolecki, Lech; Fuławka, Krzysztof; Frühwirt, Thomas; Schimmel, Martin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Measurements of seismic activity induced by mining operations are a basic tool for assessing the level of dynamic load associated with the occurrence of tremors. Knowledge of the location of the source of vibrations and the nature of seismicity is the basis for the safe planning of operations and design of both underground and surface infrastructure.
Keywords: mining-induced seismicity; seismic monitoring; MEMS; accelerometers; dynamic analysis